Antibiofilm sustainable strategies: pomegranate extract from agri-food waste as a natural antifungal against emerging Candida pathogens - Sateriale, Daniela; Forgione, Giuseppina; Raucci, Sharon; Jabbar, Abdul; Imperatore, Roberta; Germinario, Chiara; Pagliuca, Chiara; Colicchio, Roberta; Vitiello, Mariateresa; Mercurio, Mariano; Paolucci, Marina; Salvatore, Paola; et al. (Frontiers in Microbiology, 2025)
IntroductionCandida spp. infections are a leading cause of morbidity, particularly among immunocompromised and hospitalized patients. Their pathogenicity is driven by multiple virulence factors, including dimorphic transitions, germ tube formation, and biofilm development. Biofilms enhance resistance to antifungal agents and immune defenses, making biofilm-associated Candida infections a significant clinical challenge. There is an urgent need for effective and sustainable therapies, with agri-food waste emerging as a promising source of bioactive compounds.MethodsThis in vitro study evaluated the antifungal activity of a polyphenol-rich hydroethanolic pomegranate (Punica granatum L.) peel extract against clinical isolates of Candida albicans, C. glabrata, and C. parapsilosis. The extract was tested for its antimycotic effects using qualitative and quantitative assays, as well as its ability to inhibit germ tube formation and biofilm development, including adhesion and disruption of pre-formed biofilms on plastic surfaces commonly used in medical devices.ResultsThe pomegranate peel extract exhibited significant antifungal activity, demonstrating both fungistatic and fungicidal effects across all tested strains. The extract interfered with fungal membrane permeability and inhibited key virulence mechanisms, including germ tube formation and biofilm development. Notably, it reduced adhesion and disrupted established biofilms.DiscussionThese findings highlight the anti-Candida potential of pomegranate peel extract, targeting multiple virulence determinants. The results support the development of alternative therapeutic strategies against emerging biofilm-related fungal infections, leveraging sustainable approaches based on local agri-food byproducts.